2008
DOI: 10.1007/s10533-008-9234-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrology and seasonality on DOC exports from three contrasting upland catchments

Abstract: Variation in dissolved organic carbon (DOC) concentrations of surface waters is a consequence of process changes in the surrounding terrestrial environment, both within annual cycles and over the longer term. Long-term records (1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) of DOC concentrations at six catchments (0.44-10.0 km 2 ) across a climatic transect in Scotland were investigated for intra-annual relationships to evaluate potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
155
1
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(177 citation statements)
references
References 64 publications
(129 reference statements)
16
155
1
5
Order By: Relevance
“…However, this would have little sense for many reasons. First, in general: (i) studies cover very different temporal periods; (ii) the number of systems included in each individual study is very different, ranging from one intermittent stream [88] to a major comparison of 705 systems [66]; 33 of the published studies cover less than 10 systems and only 9 more than 100. Curiously, if all trends were pooled together, the existence of four earlier studies [64,66,71,73] covering a huge number of lakes in Canada and Scandinavia (1324 in total), where about 90% of the systems in each study showed no statistically significant trend, would probably give an overwhelming majority for the "non trend" category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this would have little sense for many reasons. First, in general: (i) studies cover very different temporal periods; (ii) the number of systems included in each individual study is very different, ranging from one intermittent stream [88] to a major comparison of 705 systems [66]; 33 of the published studies cover less than 10 systems and only 9 more than 100. Curiously, if all trends were pooled together, the existence of four earlier studies [64,66,71,73] covering a huge number of lakes in Canada and Scandinavia (1324 in total), where about 90% of the systems in each study showed no statistically significant trend, would probably give an overwhelming majority for the "non trend" category.…”
Section: Discussionmentioning
confidence: 99%
“…Non statistically increases and decreases are considered "no trends"; d Values only given when trend statistically significant, except when mixed in the original publication (in this case, a cautionary note is added). When value in italics, original value in other units; e [88] includes data from two streams (Loch Ard Burn 2 and Allt a'Mharcaidh) but refers to this study for DOC long term trend values; f Data from one of the catchments (Langtjern) further treated in [89] by empirical regression analysis and a process-based model; g Original units: ÎŒmol C L −1 y −1 ; h [17] show exactly the same results. They cite [9] as a source; i Original units: ÎŒeq C L −1 y −1 ; j Probably slopes for non statistically significant trends included.…”
Section: Data Quality Traceabilitymentioning
confidence: 93%
See 1 more Smart Citation
“…This release is strongly dependent on both soil temperature and moisture availability with consequent seasonal differences in periods of high and low DOC production in summer/autumn and winter/spring, respectively (Dawson et al 2008;Winterdahl et al 2011a;Peterson and Lajtha 2013). Additionally, water fluxes are of critical importance, and hydrological connection is needed to transport DOC through the landscape and into streams (Boyer et al 1996;Dawson et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, water fluxes are of critical importance, and hydrological connection is needed to transport DOC through the landscape and into streams (Boyer et al 1996;Dawson et al 2008). DOC is generated across the landscape, but areas with the highest soil carbon density are most important (Dawson et al 2011).…”
Section: Introductionmentioning
confidence: 99%